Experimental investigation for suction slots of wells turbine and shapes of point absorber - Abdullah H. Harby; Ahmed S. Shehata; Rola S. Afify; Ahmed A. Hanafy (Energy Reports, 2022)
When it comes to reducing carbon emissions, A dependable source of renewable energy is wave energy. The endless energy crisis offers a multitude of potential solutions, including wave energy. Since there are no emissions, it is energy that is good for the environment. As a renewable energy source, it is frequently used at all times. To test the effectiveness of the Wells turbine, suction slits have been used on the turbine blades in this work. The aerofoil utilized in the Wells turbine blade was NACA015. An arrangement for comparing various body types is made in the experimental buoy setup. To engage with wave motion, the setup includes a buoy that floats in the lab. Results indicated that the three slots had good pressure drop coefficient behavior, good turbine coefficient, and maximum turbine efficiency. The buoy shapes (5) and (3) for the point absorber exhibited the best properties according to the relevant parameters.